Revisão dos principais radiofármacos utilizados no Brasil e suas aplicações na detecção e terapia de patologias - Carvalho, Érico Bennemann [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Radiopharmaceuticals are substances marked with radionuclides that can be used for detection and treatment of cancer, infections and inflammatory diseases. They emit several types of radiation through different decay routes, each radioisotope with its specific properties and uses. They can usually be produced from several different materials, by bombardment with particle beams in a nuclear research reactor or cyclotron, depending on their characteristics. Brazil has four public institutions which produce - or import - and distribute radiopharmaceuticals to hospitals and clinics throughout its territory. The largest such institution, Ipen, distributes 97% of radiopharmaceuticals used in the country. Some radiopharmaceuticals decay very quickly, meaning they must be produced and quickly administered to the patient in the same location, presenting a logistical challenge. Nuclear medicine in Brazil is a promising field and has been steadily growing, although rigid laws and a lack of qualified work force hinder Research and Development efforts for new radiopharmaceuticals. The construction of a new nuclear research reactor, in 2016, should generate self-sufficiency and economy in radiopharmaceutical production and avoid a future crisis in the supply of technetium-99m, the most important radioisotope, used in over 80% of procedures with radiopharmaceuticals.

Radiofármacos são substâncias marcadas com radioisótopos, servindo para a detecção e tratamento de infecções, doenças inflamatórias e câncer. Podem emitir vários tipos de radiação através de diversas rotas de decaimento, cada um com suas propriedades e usos específicos, e serem produzidos de múltiplas maneiras, bombardeando-se diferentes materiais com feixes de partículas subatômicas, em reatores nucleares de pesquisa ou em cíclotron, dependendo de suas características. O Brasil possui quatro organizações públicas que produzem - ou importam - e distribuem radiofármacos para clínicas e hospitais de medicina nuclear por todo o território. A maior delas, o Instituto de Pesquisas Energéticas e Nucleares, distribui 97% dos radiofármacos utilizados no país. Alguns radiofármacos se degradam muito rápido, de modo que precisam ser produzidos e rapidamente administrados ao paciente no mesmo local, representando desafio logístico. A medicina nuclear no Brasil vem crescendo e é um campo promissor, ainda que leis rígidas e falta de mão-de-obra qualificada dificultam a Pesquisa e Desenvolvimento de novos radiofármacos. A construção de um novo reator nuclear de pesquisa, em 2016, deverá gerar autossuficiência e economia na produção de radioisótopos e evitar uma futura crise no fornecimento do mais importante deles, o tecnécio-99m, utilizado em mais de 80% dos procedimentos com radiofármacos.
Keywords: Radioisotopos; Radiofarmacos; Medicina nuclear; Ciclotronio; Medical physics